2022
DOI: 10.3390/biomedicines10030600
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Proteins and Susceptibility of Acinetobacter baumannii to Cefiderocol: Role of Iron Transport

Abstract: Cefiderocol, a recently introduced antibiotic, has a chemical structure that includes a cephalosporin that targets cell wall synthesis and a chlorocatechol siderophore moiety that facilitates cell penetration by active iron transporters. Analysis of the effect that human serum, human serum albumin, and human pleural fluid had on growing Acinetobacter baumannii showed that genes related to iron uptake were down-regulated. At the same time, β-lactamase genes were expressed at higher levels. The minimum inhibitor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 80 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…Finally, it has recently been suggested that in vitro susceptibility testing of cefiderocol against A. baumannii may overestimate its activity compared with conditions in vivo [ 76 ]. Specifically, cefiderocol MIC was 2- to 16-fold higher in the presence of human serum, human serum albumin, or human pleural fluid in the culture medium [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has recently been suggested that in vitro susceptibility testing of cefiderocol against A. baumannii may overestimate its activity compared with conditions in vivo [ 76 ]. Specifically, cefiderocol MIC was 2- to 16-fold higher in the presence of human serum, human serum albumin, or human pleural fluid in the culture medium [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model strains AB0057 and AYE were included among the tested strains. A previously observed increase in the AB0057 MIC to CDFC when this isolate was cultured in presence of HPF was noted 17 . However, in this case, changes in MIC were not observed under HU conditions (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…1 A,B). Previous results showed that when the AB5075, AMA16 and AB0057 CRAB strains were exposed to pure 3.5% HSA, or 4% HPF or 100% HS, fluids containing HSA, the transcriptional expression levels of these genes were down regulated for most of the conditions and strains studied 17 . The total Fe concentration was determined in 3.5% HSA and HU, achieving 72 µM; no additional iron was detected, respectively (as determined by a colorimetric iron assay kit, Sigma-Aldrich, MO, USA).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations